Street Informal Control: Parking, Preman Networks, and Local Power in Urban Indonesia - Harahap, Raegen; Desmiwar, Devi; Mujiburrahman, Mujiburrahman (Universitas Riau Kepulauan, 2025)
This study explores the phenomenon of political thuggery in the management of parking business in Pekanbaru City through a patron-client perspective. In the parking business, the patron-client relationship involves political actors, government officials, and thugs forming a network of mutual benefits. This practice has an impact on increasing social injustice and hampers transparent parking governance. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and document analysis. The results of the study showed that patrons provided legal and political protection to clients who were in charge of managing and securing parking areas informally. This study recommends the digitization of the parking system, strengthening regulations, and the involvement of civil society to break the chain of thuggery. This reform is expected to create fairer and more sustainable parking governance.